HIGH SCHOOL STUDENTS' CREATIVE THINKING ABILITY IN PROPOSING COLLABORATIVE PROBLEMS ON SEQUENCES AND SERIES - Nabilla Dihni Amilia; Tatag Yuli Eko Siswono; Endah Budi Rahaju (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study aims to describe the creative thinking ability of high school students in posing collaborative problems on sequences and series, so the type of research used is a case study with a qualitative approach. The subjects in this study were high school students of grade X who were divided into groups of students with high, medium, and heterogeneous mathematical abilities (high, medium, and low). There are four data collection techniques used in this study, namely the mathematics ability test (TKM), the collaborative mathematics problem posing task (TPMKM), observation, and interviews. The instruments in this study are divided into two, namely the main instrument and supporting instruments. The main instrument is the researcher, while the supporting instruments are in the form of the mathematics ability test grid (TKM), the collaborative mathematics problem posing task sheet (TPMKM), observation guidelines, and interview guidelines. The collected data were then analyzed into three stages: data condensation, data presentation, and conclusion drawing. Data validity checking in this study uses method triangulation. There are two methods used in checking the validity of the data, namely researcher observation and FGD. The results of the study found that in homogeneous groups, the high homogeneity group demonstrated creative thinking skills in the form of fluency, flexibility, and novelty when posing collaborative problems, while the medium homogeneity group only demonstrated fluency and flexibility. In heterogeneous groups, the researchers found that student groups only demonstrated fluency. The different creative thinking skills of each group were due to differences in the composition of the mathematical abilities of the group members.